Minimally Invasive Approach versus Sternotomy for Bentall Procedure: A Single-Center Experience - Hong-Peng Zou; Feng Lu; Xiang Long; Shu-Qiang Zhu; Kun Lin; Bai-Quan Qiu; Xin Yang; Jian-Jun Xu; Yong-Bing Wu (Journal of Interventional Cardiology, 2024)
Background. The need for minimally invasive Bentall surgery for the treatment of aortic lesions with aortic insufficiency is increasing; however, comparative studies on the safety of the minimally invasive Bentall procedure and sternotomy Bentall procedure are lacking. Methods. Clinical data of 56 patients who underwent the Bentall procedure performed by the same surgical team at our center between December 2018 and December 2021 were retrospectively analyzed and followed up for 6 months after discharge. After dividing the patients into a right anterior chest minimally invasive Bentall surgery (RAT-Bentall) group (n = 13) and a conventional sternotomy Bentall surgery (C-Bentall) group (n = 43), intraoperative and early postoperative clinical data and echocardiography at 6 months after discharge were compared. Results. Compared with the C-Bentall group, the RAT-Bentall group had a lower postoperative visual analogue scale (VAS) pain score [(3.00 ± 2.08) VS (5.77 ± 1.84), P<0.001] and a shorter CSICU hospital stay [(1.90 ± 0.52) VS (2.51 ± 1.58) d, P<0.001] and postoperative hospital stay [(7.62 ± 1.81) VS (10.42 ± 2.45) d, P=0.035]. The incidence of postoperative complications and echocardiographic at 6-month follow-up after discharge was not statistically different between the two groups. Conclusion. The RAT-Bentall procedure is safe and effective. Compared with the sternotomy Bentall procedure, it can reduce postoperative pain as well as patients’ CSICU and postoperative hospital stay. Therefore, this technology is worth promoting and applying.